Nutrition Awareness of Middle School Students in the Early Adolescence Period - Merve Ok; Nisa Yenikalayci; Gonca Harman (Journal of Science Learning, 2023)
Healthy nutrition is essential in preventing possible diseases and treating existing diseases by controlling their course. Based on this importance, adolescence is one of the periods to be considered. Adolescence is a fundamental determinant of healthy life in adulthood and old age. Healthy nutrition awareness gained in this period will raise awareness of the adolescent individual herself/himself and the people around her/him. This research aimed to determine the nutrition awareness of middle school students in early adolescence. According to the phenomenology, the research was conducted with eight volunteer students in the 8th grade in a public middle school in the Central Anatolia region in Turkey. Data were collected through semi-structured interviews with each student individually using the "Interview Form about Nutrition Awareness in Adolescence Period" prepared by the researchers. The data were analyzed by using content analysis. As a result of the research, it was determined that the nutrition awareness of middle school students in the early adolescence period was low. In this context, increasing middle school students' nutrition awareness was recommended.